A 189 MHz, 2400 deg2 polarization survey with the Murchison widefield array 32-element prototype - Bernardi, G .; Greenhill, L.; Mitchell, D.; Ord, S.; Hazelton, B.; Gaensler, B.; de Oliveira-Costa, A.; Morales, M.; Udaya Shankar, N.; Subrahmanyan, R.; Wayth, Randall; Lenc, E.; et al. (Institute of Physics Publishing, Inc., 2013)
We present a Stokes I, Q and U survey at 189 MHz with the Murchison Widefield Array 32 element prototype covering 2400 deg2. The survey has a 15.6 arcmin angular resolution and achieves a noise level of 15 mJy beam–1. We demonstrate a novel interferometric data analysis that involves calibration of drift scan data, integration through the co-addition of warped snapshot images, and deconvolution of the point-spread function through forward modeling. We present a point source catalog down to a flux limit of 4 Jy. We detect polarization from only one of the sources, PMN J0351-2744, at a level of 1.8% ± 0.4%, whereas the remaining sources have a polarization fraction below 2%. Compared to a reported average value of 7% at 1.4 GHz, the polarization fraction of compact sources significantly decreases at low frequencies. We find a wealth of diffuse polarized emission across a large area of the survey with a maximum peak of ~13 K, primarily with positive rotation measure values smaller than +10 rad m–2. The small values observed indicate that the emission is likely to have a local origin (closer than a few hundred parsecs). There is a large sky area at α >= 2h30m where the diffuse polarized emission rms is fainter than 1 K. Within this area of low Galactic polarization we characterize the foreground properties in a cold sky patch at (α, δ) = (4h, –27°.6) in terms of three-dimensional power spectra.